The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1159/000097757
|View full text |Cite
|
Sign up to set email alerts
|

A Placebo-Controlled Trial of Valproate for Agitation and Aggression in Alzheimer’s Disease

Abstract: Background/Aims: To assess the efficacy and tolerability of valproate for the treatment of agitation and aggression in moderate-to-severe Alzheimer’s disease (AD). Methods: This was a randomized, double-blind, placebo-controlled crossover trial of valproate in institutionalized AD patients. Patients were assessed with the Neuropsychiatric Inventory (NPI) and Cohen-Mansfield Agitation Inventory at baseline and after 6 weeks of treatment with valproate and placebo, with 2 weeks between phases to allow for placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 40 publications
0
70
0
Order By: Relevance
“…In patients with mild to moderate AD, divalproex treatment (10-12 mg/kg/day) did not delay the emergence of agitation and cognitive impairment and, more alarmingly, was found to accelerate brain volume loss with significant toxic effects (Tariot et al, 2011). VPA treatment was also found to be ineffective for the management of agitation and aggression in older patients with moderate to severe AD (Herrmann et al, 2007). Of note, most of these reports used fixed doses and had few data on VPA's effects on the pathogenesis or neuropathology of AD.…”
Section: Admentioning
confidence: 99%
“…In patients with mild to moderate AD, divalproex treatment (10-12 mg/kg/day) did not delay the emergence of agitation and cognitive impairment and, more alarmingly, was found to accelerate brain volume loss with significant toxic effects (Tariot et al, 2011). VPA treatment was also found to be ineffective for the management of agitation and aggression in older patients with moderate to severe AD (Herrmann et al, 2007). Of note, most of these reports used fixed doses and had few data on VPA's effects on the pathogenesis or neuropathology of AD.…”
Section: Admentioning
confidence: 99%
“…It inhibits GSK3β, but has additional effects by acting as a transcriptional modulator through the inhibition of HDACs, and by reducing excitotoxicity 110,113 . While valproate might not be suited for the management of agitation in dementia 114 , longer-term studies are necessary to be able to judge its neuroprotective effects. PP1/PP2A phosphatase inhibition is a possible strategy to boost phosphorylation of mHtt in HD and reduce its toxicity 108 .…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Individual practitioners may use practice-based evidence to guide their therapeutic decisions. Several recent trials suggest that use of valproate to treat agitation has no superiority over placebo and is associated with substantial toxicity Herrmann et al 2007). Early trials suggested the benefit of carbamazepine as a treatment for agitation (Tariot et al 1998).…”
Section: Use Of Psychotropic Agents To Treat Behavioral Disturbances mentioning
confidence: 99%